Level of Testosterone, Libido, and Sperm Quality of Bligon, Kejobong, and Etawah Cross-Bred Bucks - Rachmawati, L; Ismaya, Ismaya; Astuti, Pudji (ANIMAL PRODUCTION, 2013)
The aim of the study was to investigate the comparison and correlation among testosterone concentrations, libido, and sperm quality of Bligon, Kejobong, and Etawah Cross-bred (PE) bucks at similar age, feed, and season. Samples used were 9 bucks (3 Bligon, 3 Kejobong, and 3 PE) of approximately 18 months of age. The testosterone was measured by enzyme-linked immunosorbent assay (ELISA) method. Libido observation was quantified at the first time of sniffing, mounting, and finally ejaculation. Sperm was collected by using artificial vagina. The reesults showed that Kejobongâs testosterone in the morning (12.00Â±6.56 ng/ml) was significantly different compared to PE (6.82Â±4.18 ng/ml), whereas Bligonâs testosterone in the morning (9.23Â±4.73 ng/ml) was similar compared to Kejobong and PE. The best time of Kejobongâs libido was in the morning (6.77Â±5.96; 11.27Â±8.10, and 18.45Â±8.27 sec.) and in the afternoon (8.89Â±7.97; 11.03Â±8.74, and 21.05Â±9.60 sec.). The motility and concentrations of Kejobongâs spermatozoa (75.67Â±6.51% and 5838.67Â±140.90 x106/ml) were significantly different compared to Bligon (60.67Â±9.61% and 4625.33Â±129.72 x106/ml) and PE (63.13Â±8.33% and 3756.00Â±52.76 x106/ml. It could be concluded that Bligon and PE bucks have the similar testosterone concentration, and the libido and sperm quality of Kejobong is better than Bligon and PE bucks.Â Animal Production 15(2):76-82, May 2013